Sound - Perception - Performance - Bader, Rolf.; SpringerLink (Online service) (Heidelberg : Springer International Publishing : Imprint: Springer, 2013)
Musical Performance covers many aspects like Musical Acoustics, Music Psychology, or motor and prosodic actions. It deals with basic concepts of the origin or music and its evolution, ranges over neurocognitive foundations, and covers computational, technological, or simulation solutions. This volume gives an overview about current research in the foundation of musical performance studies on all these levels. Recent concepts of synchronized systems, evolutionary concepts, basic understanding of performance as Gestalt patterns, theories of chill as performance goals or historical aspects are covered. The neurocognitive basis of motor action in terms of music, musical syntax, as well as therapeutic aspects are discussed. State-of-the-art applications in performance realizations, like virtual room acoustics, virtual musicians, new concepts of real-time physical modeling using complex performance data as input or sensor and gesture studies with soft- and hardware solutions are presented. So although the field is still much larger, this volume presents current trends in terms of understanding, implementing, and perceiving performance.
Production and Perception Models -- Neurocognition and Evolution -- Applications.
Keywords: Engineering; Acoustics; Acoustics in engineering; Music; Engineering; Engineering Acoustics; Acoustics; Music; Computational Intelligence